2018
DOI: 10.1112/topo.12056
|View full text |Cite
|
Sign up to set email alerts
|

L2-Betti numbers of totally disconnected groups and their approximation by Betti numbers of lattices

Abstract: The main result is a general approximation theorem for normalised Betti numbers for Farber sequences of lattices in totally disconnected groups. Further, we contribute to the general theory of L2‐Betti numbers of totally disconnected groups and provide exact computations of the L2‐Betti numbers of the Neretin group and Chevalley groups over the field of Laurent series over a finite field and their lattices.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…To even state Theorem 1 in that generality, recent advances in the theory of ℓ 2 -Betti numbers were necessary. ℓ 2 -Betti numbers of discrete groups enjoy a long history but it was not until recently that ℓ 2 -Betti numbers were defined for arbitrary unimodular lcsc groups by Petersen [19], and a systematic theory analogous to the discrete case emerged [13,19,20]. Earlier studies of ℓ 2 -Betti numbers of locally compact groups in specific cases can be found in [4,6,10].…”
Section: Introductionmentioning
confidence: 99%
“…To even state Theorem 1 in that generality, recent advances in the theory of ℓ 2 -Betti numbers were necessary. ℓ 2 -Betti numbers of discrete groups enjoy a long history but it was not until recently that ℓ 2 -Betti numbers were defined for arbitrary unimodular lcsc groups by Petersen [19], and a systematic theory analogous to the discrete case emerged [13,19,20]. Earlier studies of ℓ 2 -Betti numbers of locally compact groups in specific cases can be found in [4,6,10].…”
Section: Introductionmentioning
confidence: 99%
“…It is based on the new notion of relative soficity. We will not discuss approximation for sequences of lattices in locally compact groups as in [1,19].…”
Section: Introductionmentioning
confidence: 99%
“…In [96] H. D. Petersen, R. Sauer and A. Thom present a general Lück approximation theorem for normalised Betti numbers for Farber sequences of lattices in totally disconnected groups. (see [23] for the definition of R[ [G]] and its properties…”
Section: Other Variations Of the Lück Approximationmentioning
confidence: 99%